The demand for unfair gambles: Why illegal lotteries persist - Desiree A. Desierto; John V. C. Nye; Jema M. Pamintuan (University of the Philippines, School of Economics (UPSE), 2011)
We show how cheating in illegal gambling can be sustained in equilibrium, even when gamblers are aware of it. Not only is cheating profit-maximizing for operators, but it can also be utility-maximizing if it provides gamblers the opportunity to engage in other related activities that generate non-monetary rewards, such as practicing superstitions. This, in turn, suggests why legalizing gambling might not fully capture the gains from the illegal market - operators and gamblers both prefer cheating, but this would be harder to hide in a legalized environment. We illustrate the model, generate results, and verify them empirically, using the example of jueteng, an illegal numbers game in the Philippines.
Keywords: 330